A Hyperbranched Disulfide Polymer as Cathode Material for Lithium-Ion Batteries. Issue 7 (1st January 2018) - Liu, Xu; Wang, Ailian; Wang, Shi; Liu, Xiaoping; Chen, Jie; Xu, Hao; Zeng, Qinghui; Zhang, Liaoyun
Abstract : A new hyperbranched disulfide polymer with S-S bond and triazinebenzeneamine, named hyperbranched polytriazinediaminodiphenyl disulfide (HPDADS), was firstly synthesized by a convenient A2 +B3 approach. Benefitting from this particular topological structure, this type of the hyperbranched disulfide polymer had excellent solubility in common organic solvent such as NMP. The result of the thermosgravimetric analysis (TGA) indicated that the obtained HPDADS had high thermal stability. When the hyperbranched disulfide polymer was utilized for cathode active materials for rechargeable lithium battery, it exhibited a reversible redox behavior. The charge–discharge test showed an initial discharge capacity of 186 mA h g −1 at 0.1 C, and the highest discharge capacity of 219 mA h g −1 at 10 th cycle. In addition, HPDADS/Li batteries delivered good cycling performance and rate capability. To the best of our knowledge, this is the first report about hyperbranched disulfide polymer for cathode materials applied in lithium-ion battery. This research can open a new field of disulfide cathode materials and provide a new idea for avenues of further research to advanced lithium–ion battery technologies.